The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1089/ars.2021.0086
|View full text |Cite
|
Sign up to set email alerts
|

Thiol Isomerases Orchestrate Thrombosis and Hemostasis

Abstract: Thiol isomerases orchestrate thrombosis and haemostasis. Antioxidants & Redox Signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 146 publications
0
6
0
Order By: Relevance
“…These residues are often buried from solvent exposure [20]. Cysteines can also be in their free thiol state, where they are exposed to solvent and play non-structural roles, including regulation of enzyme activity (e.g., in kinases) [21,22], metal binding (e.g., Zn-finger transcriptional factors) [23], catalytic redox reactions (e.g., thiol isomerases as described in Section 3) [24,25], and catalytic nucleophilic reactions (e.g., caspases and phosphatases) [26]. The nucleophilicity of the thiol is determined by the stabilization of the negatively charged thiolate [27], a physicochemical property of the sulfur atom.…”
Section: The Biochemistry Of Cysteines 21 Cysteine Reactivity: Not Al...mentioning
confidence: 99%
See 1 more Smart Citation
“…These residues are often buried from solvent exposure [20]. Cysteines can also be in their free thiol state, where they are exposed to solvent and play non-structural roles, including regulation of enzyme activity (e.g., in kinases) [21,22], metal binding (e.g., Zn-finger transcriptional factors) [23], catalytic redox reactions (e.g., thiol isomerases as described in Section 3) [24,25], and catalytic nucleophilic reactions (e.g., caspases and phosphatases) [26]. The nucleophilicity of the thiol is determined by the stabilization of the negatively charged thiolate [27], a physicochemical property of the sulfur atom.…”
Section: The Biochemistry Of Cysteines 21 Cysteine Reactivity: Not Al...mentioning
confidence: 99%
“…They are essential for protein folding and are thus essential to life. Thiol isomerases contain thioredoxin-like domains that contain a CXXC motif within their catalytic site for mediating oxidative protein folding [25]. Cysteines within the CXXC motif are among the most susceptible to electrophilic attack by oxidants and are some of the most reactive cysteines in the entire proteome [116].…”
Section: Thiol Isomerases Convert Redox Cues To a Thrombotic Responsementioning
confidence: 99%
“…showed that ERp57/PDIA3 oxidatively inactivates human transglutaminase 2, thus defining a reversible protein-controlled redox switch system [ 92 ]. Two recent reviews analyzed the role of the thiol isomerase “system” as positive and negative regulators that contribute to redox homeostasis, maintenance of normal hemostasis, vascular integrity [ 94 ], and regulation of thrombotic events [ 95 ].…”
Section: Localization and Functions Of Erp57/pdia3 Outside Of The Ermentioning
confidence: 99%
“…Years ago, a study on the antithrombotic activity of red wine and red grape juice showed that natural components of wine act as PDI inhibitors and, to a lesser extent, as ERp57/PDIA3 inhibitors [ 123 ]. More recently, Gaspar and Gibbins analyzed the function of thiol isomerases in thrombosis and hemostasis and summarized the known PDI inhibitors, showing that often these inhibitors are not so selective for a specific PDI family member [ 95 ].…”
Section: High-impact Information On Erp57/pdia3 (Ligand)mentioning
confidence: 99%
See 1 more Smart Citation